Blended Learning in the Foundational Design Studio - Dabaghi, Karma (2022)
Based on our experience of teaching the first-year Foundation studio online in an architecture program, we highlight the benefits of Blended Learning that incorporates strategic scheduling of physical and virtual delivery modes. Our qualitative observations build on recent literature that examines the use of online elements in teaching the design studio. We observed that the more theoretical aspects appear to be effectively mastered online while the practical ones that require tactile abilities are not. We identify what kinds of interaction maximize the potential of Technology Enhanced Learning (TEL) in the Foundation studio.